Microfluidic Diagnostics of the Impact of Local Microfracture Connectivity on Hydrocarbon Recovery Following Water Injection. Issue 7 (2nd July 2020) - Du, Yujing; Mehmani, Ayaz; Xu, Ke; Kelly, Shaina; Balhoff, Matthew; Torres‐Verdín, Carlos
Abstract: Microfractures originate in hydrocarbon reservoirs and groundwater aquifers either in the form of pore‐scale authigenic apertures or secondary openings during well stimulation. Microfractures are often difficult to detect and can act as an invisible impediment when predicting hydrocarbon recovery. We use microfluidics to identify the flow conditions at which microfracture connectivity with macrofractures becomes impactful. The analysis focuses on fluid displacements at unfavorable mobility ratios, which are difficult to capture with high‐order numerical methods. Two configurations of microfracture type with the porous matrix, either dead‐end (only connected to one macrofracture) or connecting two macrofractures, were investigated as case examples for both water and oil‐wet conditions. Our findings confirm that improvements in hydrocarbon recovery are not universal due to the presence of microfractures but rather are a function of capillary number, wettability, and microfracture connectivity. We find that, regardless of wettability, a capillary number threshold for a connected microfractured system exists beyond which the effects of microfractures on recovery, fluid dendrite morphology, and oil ganglia number diminish considerably. However, substantial geometry‐dependent differences in recovery are observed below this threshold. A connected microfracture generally decreases hydrocarbon recovery and suppresses coalescence of viscous fingering dendrites regardless of wettability. In contrast, a dead‐end microfracture causes wettability‐dependent effects with (1) minimal impact on hydrocarbon recovery at water‐wet conditions and (2) both decreasing and increasing recovery effects at oil‐wet conditions. Furthermore, dead‐end microfractures become somewhat impactful to the divergence of viscous dendrites when capillary number increases but are overall ineffective to the trapped ganglia numbers. Key Points: Microfractured systems present three distinct viscous fingering generation mechanisms Capillary number and microfracture connectivity are more impactful in creating a viscous fingering generation mechanism than wettability Although dead‐end microfractures adopt unique dendrite generation mechanisms, their impacts on recovery are minimal at water‐wet conditions